Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N; Pemonge, M.-H. H; Ouassou, A; Sbay, H; Kremer, A; Petit, R J (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics